Rapid Action of Aldosterone on Protein Levels of Sodium-Hydrogen Exchangers and Protein Kinase C Beta Isoforms in Rat Kidney - Somchit Eiam-Ong; Mookda Chaipipat; Krissanapong Manotham; Somchai Eiam-Ong (International Journal of Endocrinology)
Previous in vitro studies demonstrated that aldosterone rapidly activates sodium-hydrogen exchangers 1 and 3 (NHE 1 and 3). In vitro investigations revealed that protein kinase C (PKC) regulates NHE properties. We previously demonstrated that aldosterone rapidly enhances PKCα protein abundance in the rat kidney. There are no reports of renal PKCβ (I and II) protein levels related to the regulation by aldosterone. There are also no in vivo data regarding the rapid effects of aldosterone on renal protein levels of NHE (1 and 3) and PKCβ (I and II), simultaneously. In the current study, rats received normal saline solution or aldosterone (150 μg/kg BW, i.p.). After 30 minutes, abundance and immunoreactivity of these proteins were determined by Western blot analysis and immunohistochemistry, respectively. Aldosterone increased NHE1 and NHE3 protein abundance to 152% and 134%, respectively (P<0.05). PKCβI protein level was enhanced by 30%, whereas PKCβII declined slightly. Aldosterone increased NHE protein expression mostly in the medulla. PKCβI immunostaining intensity was increased in the glomeruli, renal vasculature, and thin limb of the loop of Henle, while PKCβII was reduced. This is the first in vivo study to simultaneously demonstrate that aldosterone rapidly elevates PKCβI and NHE (1 and 3) protein abundance in the rat kidney. Aldosterone-induced NHE (1 and 3) protein levels may be related to PKCβI activation.